2021
DOI: 10.15587/1729-4061.2021.225325
|View full text |Cite
|
Sign up to set email alerts
|

Developing an algorithm to minimize boolean functions for the visual-matrix form of the analytical method

Abstract: This research has established the possibility of improving the effectiveness of the visual-matrix form of the analytical Boolean function minimization method by identifying reserves in a more complex algorithm for the operations of logical absorption and super-gluing the variables in terms of logical functions. An improvement in the efficiency of the Boolean function minimization procedure was also established, due to selecting, according to the predefined criteria, the optimal stack of logical operations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…It was noted that the reported method for synthesizing symmetrical functions is the first, which is aimed at reducing the depth of logical schemes generated for symmetrical Boolean functions. The experimental results demonstrated that the approach in question reduces the depth of the final implementation of the function to 25.93 % compared to other methods of synthesis of symmetrical functions.…”
Section: Literature Review and Problem Statementmentioning
confidence: 98%
“…It was noted that the reported method for synthesizing symmetrical functions is the first, which is aimed at reducing the depth of logical schemes generated for symmetrical Boolean functions. The experimental results demonstrated that the approach in question reduces the depth of the final implementation of the function to 25.93 % compared to other methods of synthesis of symmetrical functions.…”
Section: Literature Review and Problem Statementmentioning
confidence: 98%
“…This determines the need to investigate equivalent figurative transformations in order to minimize logic functions on the Reed-Muller basis. In particular, the peculiarities of relatively complex algorithms of simplification of functions with the procedure of inserting the same conjuncterms of polynomial functions followed by the operation of super-gluing the variables, a stack of logical operations for the first binary matrix of a polynomial function [9], ways to simplify arbitrary functions in the Reed-Muller basis.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…This is a sufficient resource to minimize functions and makes it possible to do without auxiliary objects, such as Karnaugh maps, Weich diagrams, acyclic graph, non-directed graph, coverage tables, cubes, etc. The clarity of 2-dimensional binary matrices allows one to manually simplify Boolean functions (using a mathematical editor, such as MathType 7.4.0) within up to 64 input variables [9] for PESOP (DCNF) representation of the function.…”
Section: Table 11mentioning
confidence: 99%
See 2 more Smart Citations